Enhancing Quality of Drying Mixed Shrimp Paste from Karawang with Red Pigment by Angkak - Dessy Agustina Sari; Muhamad Djaeni; Azafilmi Hakiim; Sukanta Sukanta; Nurul Asiah; Didik Supriyadi (IPTEK The Journal for Technology and Science, 2018)
existence of shrimp paste farmer is supported by activities of auction fish place one of which located Ciparage beach, Karawang – West Java. Perpetrators produced 2 products such as shrimp paste and mixed shrimp paste. Utilization of Rebon shrimp by totality does not need other additives because drying process brings out the color that had itself so final product becomes redness. Involvement of Petek fish almost partially could reduce the color quality so the society used Rhodamine-B dye. This is widely spreading in the area because this matter is distributed by seller directly – door to door and the price is affordable – cheaper. Novelty this research is application of tray dryer with operating temperature variables – 40, 50, 60oC for 7 hours and the presence of Angkak as natural the red pigment that it is safe for human health. The results showed that the optimum condition of drying mixed shrimp paste was achieved by temperature 40oC. This is not about how much and quickly the moisture that evaporating into the air. Paradigm to chemical composition – organoleptic and antioxidant activity – DPPH method also was be consideration for that matter. Physically, this dried product had normal smell, salty taste, brown color, soft texture, solid shape, and normal appearance.